Factors Contributing to Survival, Condition, and Quality of Edible Akoya Oysters, Pinctada Fucata (Gould, 1850). - Vaisey, Megan Rose Walton (Curtin University, 2025)
The Akoya oyster (Pinctada fucata), has recently been of interest as a food product in Western Australia. Whilst the production of Akoya has been largely successful in terms of production, little is understood about how edible quality is impacted by external factors throughout the supply chain for this species. This work included two laboratory experiments and collation of field experimental data which assessed how different environmental, harvest and processing parameters influenced overall health and edible quality of Akoya oyster.